On a Third-Order Three-Point Boundary Value Problem. (3rd July 2012) - Guezane-Lakoud, A.; Hamidane, N.; Khaldi, R.
Abstract : We consider a third-order three-point boundary value problem. We introduce a generalized polynomial growth condition to obtain the existence of a nontrivial solution by using Leray-Schauder nonlinear alternative, then we give an example to illustrate our results.